Design of Rectangular Patch Microstrip Antenna with Defected Ground Structure Method at 3.5 GHz Frequency for 5G Technology - Galuh Kartikasari; Muhammad Panji Kusuma Praja; Shinta Romadhona (Journal of Information Technology and Its Utilization, 2023)
5G technology is currently developing rapidly in various countries. 5G technology has three sub-frequencies: low band, midband and high band. Midband frequencies in Indonesia are between 2.6 GHz and 3.5 GHz. In order for 5G technology is able to be used in Indonesia, it needs an antenna that can work at 3.5 GHz and has a wide bandwidth. Microstrip antenna is a simple and efficient antenna. However, microstrip antenna has minimal bandwidth. To overcome this, certain methods are needed, one of which is the defected ground structure (DGS) method. The initial design of the antenna has dimensions according to the results of the calculation formula. Then optimization is carried out by reducing the dimensions of the antenna components. After that, the DGS method is applied to widen the bandwidth. The initial design of the single-patch antenna before using the DGS method has a return loss value of -19.96 dB, VSWR 1.22, with a gain value of 3.812 dB and bandwidth 105.1 MHz. The simulation results of the antenna using DGS have a return loss value of -39.76 dB, VSWR of 1.02, with a gain value 3.16 dB and a bandwidth of 158.4 MHz. These results prove that the use of the DGS method can increase bandwidth.